Pengaruh Literasi Keuangan, Pengendalian Diri dan Teman Sebaya Terhadap Perilaku Konsumtif Pada Generasi Z di Kabupaten Tegal: The Influence of Financial Literacy, Self-Control and Peers on Consumptive Behavior in Generation Z in Tegal Regency - Mar'ah, Sakinatul; Gumilar, Gugum; Gumilar, Rendra; Widyaningrum, Bakti (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to examine the effect of financial literacy, self-control and peers on consumptive behavior in Generation Z in Tegal Regency. A quantitative approach was used in this study with a survey method by distributing questionnaires to 100 respondents using the purposive sampling technique. The data was analyzed using multiple linear regression with the help of SPSS version 22 software. The results showed that financial literacy had no effect on consumptive behavior, with a t-value of 1.478 and a significance of 0.143 (p > 0.05). Self-control has a significant negative effect on consumptive behavior, with a t-value of -2.442 and a significance of 0.016 (p <0.05), which means that the higher the level of self-control, the lower the consumptive behavior. Peers have a positive and significant effect on consumptive behavior with a t-value of 9.705 and a significance of 0.000 (p <0.05), which means that the higher the interaction with peers, the higher the consumptive behavior. The coefficient of determination (R²) is 0.528, indicating that financial literacy, self-control, and peers have an effect of 52.8% on consumptive behavior, while the rest is influenced by other factors outside the research model.